1999
DOI: 10.1359/jbmr.1999.14.8.1379
|View full text |Cite
|
Sign up to set email alerts
|

FokI Polymorphism at Translation Initiation Site of the Vitamin D Receptor Gene Predicts Bone Mineral Density and Vertebral Fractures in Postmenopausal Italian Women

Abstract: A novel T/C polymorphism (ATG to ACG) at the translation initiation site of the vitamin D receptor (VDR) gene, defined by FokI restriction endonuclease, has been recently associated with variation in bone mineral density (BMD) and rates of bone loss in a group of postmenopausal Mexican-American women. The presence of the restriction site, designated as f, allows protein translation to initiate from the first ATG, while the allele lacking the site, indicated as F, initiates translation at a second ATG. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
2
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 39 publications
7
45
2
4
Order By: Relevance
“…These results are consistent with an initial report on postmenopausal Caucasian Mexican-American women, which showed a 12.8% lower lumbar spine BMD in 15 ff homozygous women than in 37 FF homozygous women (Gross et al 1996). Moreover, our results are also in accord with a previous study in postmenopausal Italian women, which demonstrated a weak association between the FokI polymorphism and lumbar BMD (P ϭ 0.06) but no association with femoral neck BMD (Gennari et al 1999).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with an initial report on postmenopausal Caucasian Mexican-American women, which showed a 12.8% lower lumbar spine BMD in 15 ff homozygous women than in 37 FF homozygous women (Gross et al 1996). Moreover, our results are also in accord with a previous study in postmenopausal Italian women, which demonstrated a weak association between the FokI polymorphism and lumbar BMD (P ϭ 0.06) but no association with femoral neck BMD (Gennari et al 1999).…”
Section: Discussionsupporting
confidence: 93%
“…The initial study by Gross et al (1996), conducted in postmenopausal Caucasian Mexican-American women, showed a 12.8% lower lumbar spine BMD in 15 ff homozygous women when compared with 37 FF homozygous women, and also showed an increased bone loss rate from the femoral neck in ff women when compared with FF women, as observed during a 2-year period. Another study, of postmenopausal Italian women, also showed a weak association between the FokI polymorphism and lumbar BMD (P ϭ 0.060), but no association with femoral neck BMD (Gennari et al 1999).…”
Section: Introductionmentioning
confidence: 94%
“…Gross et al [15] conducted a study in postmenopausal Mexican-American women, showed that FokI polymorphism of the VDR gene correlates significantly with decreased BMD at the lumbar spine and an increased rate of bone loss at the hip in ff subjects. In another study of postmenopausal Italian women population, Gennari L [16] observed a weak association between FokI polymorphism and lumbar BMD (p = 0.06) but no reveland to femoral neck BMD(p = 0.5). Base on VDR biological functions, FokI can be seen as a candidate gene for osteoporosis.…”
Section: Introductionmentioning
confidence: 91%
“…Five studies [16,[22][23][24][25] were performed in Caucasians and another five investigations [26][27][28][29][30] were conducted in Asians. Furthermore, two reports [14,31] were from mixed ethnicities.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…8 Polymorphism at the ATG initiation codon (FokI site) has been associated with genetic determination of final height in Japanese subjects, with heterozygotes at this locus achieving a greater final height than homozygotes for either allele, 1 and with heritable variation in bone mineral density. 9 Polymorphism at both the FokI and TaqI sites has been associated with variation in intervertebral disc degeneration in males. 10 The VDR is also found in both normal and neoplastic haemopoietic cells.…”
mentioning
confidence: 99%